2018
DOI: 10.3390/tropicalmed3020062
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis in Africa: Time to Uncover the True Disease Load

Abstract: Melioidosis is an often fatal infectious disease with a protean clinical spectrum, caused by the environmental bacterial pathogen Burkholderia pseudomallei. Although the disease has been reported from some African countries in the past, the present epidemiology of melioidosis in Africa is almost entirely unknown. Therefore, the common view that melioidosis is rare in Africa is not evidence-based. A recent study concludes that large parts of Africa are environmentally suitable for B. pseudomallei. Twenty-four A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Southeast Asia and Northern Australia are hyperendemic regions (Cheng and Currie, 2005). However, reports of environmental B. pseudomallei isolates or melioidosis cases from Central and South America, Africa and South Asia indicate that the bacteria are found in the tropics worldwide (Mukhopadhyay et al, 2018; Rolim et al, 2018; Steinmetz et al, 2018; Torres et al, 2018). Furthermore, a recent comprehensive modeling study suggests vast underreporting of melioidosis cases and highlights the need to assess the true global burden and epidemiology of the disease (Limmathurotsakul et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Southeast Asia and Northern Australia are hyperendemic regions (Cheng and Currie, 2005). However, reports of environmental B. pseudomallei isolates or melioidosis cases from Central and South America, Africa and South Asia indicate that the bacteria are found in the tropics worldwide (Mukhopadhyay et al, 2018; Rolim et al, 2018; Steinmetz et al, 2018; Torres et al, 2018). Furthermore, a recent comprehensive modeling study suggests vast underreporting of melioidosis cases and highlights the need to assess the true global burden and epidemiology of the disease (Limmathurotsakul et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“… 20 To our knowledge, there have not been data published on B. pseudomallei seropositivity in Tanzania. 21 In Uganda, a study by Frazer 22 identified 25 (5.9%) of 426 individuals as seropositive to B. pseudomallei using IHA. The Frazer study surveyed healthy adults from the capital, Kampala, as well as rural areas, and most seropositive participants had reciprocal antibody titers ≤ 160.…”
Section: Discussionmentioning
confidence: 99%
“…A notion of play in a marshy area was found at home. The environmental study 2 years in the screen isolated positive signals for Burkholderia pseudomallei in the vicinity [2] . This same case has been under a transfusion exchange program for 11 months and in addition he was transfused twice during his hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestation varies from mild localized infection to fulminant sepsis. Melioidosis and its germ are increasingly reported on the African continent and particularly in Central Africa, possibly due to the increased awareness of clinicians and microbiologists and the growing recognition of the organism [2] . Burkholderia pseudomallei is a Gram-negative bacillus found in soil.…”
Section: Introductionmentioning
confidence: 99%